THE ADVANTAGE OF CUSTOMER RELATIONSHIP MANAGEMENT IN INCREASING A COMPANY'S INCOME AND REDUCING EXPENDITURES - Ristanti Akseptori; Inas Safina Bobsaid (Universitas Dinamika, 2022)
It is imperative that a company's customer relationship management (CRM) strategy places a focus on steadily elevating the quality of service that is offered to the company's clientele in order for the business to achieve financial and operational success. The consumers' impressions of the company may be influenced by supporters, who can also inform, instruct, and enlighten them about the various available choices. It is not entirely out of the realm of possibility for a firm to profit from social turmoil by using a variety of different technological strategies. Programs that are intended to maintain consumers as repeat clients are variously referred to as recurrent marketing programs, club participation programs, and customer loyalty programs. All of these programs are essentially the same thing. When a company is able to properly manage its connections with its clients, they see a decrease in the number of customers who opt to discontinue doing business with that particular company. This is because the firm is better able to maintain positive relationships with its clientele. This is due to the fact that satisfied consumers are more inclined to speak positively about a certain firm to other people. The use of CRM paves the way for the company to obtain better levels of income while simultaneously minimizing the levels of operational expenses it incurs.